2012
DOI: 10.1021/jp304723w
|View full text |Cite
|
Sign up to set email alerts
|

RNA–Magnesium–Protein Interactions in Large Ribosomal Subunit

Abstract: Some of the magnesium ions in the ribosome are coordinated by multiple rRNA phosphate groups. These magnesium ions link distal sequences of rRNA, primarily by incorporating phosphate groups into the first coordination shell. Less frequently, magnesium interacts with ribosomal proteins. Ribosomal protein L2 appears to be unique by forming specific magnesium-mediated interactions with rRNA. Using optimized models derived from X-ray structures, we subjected rRNA/magnesium/water/rProtein L2 assemblies to quantum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 56 publications
0
58
0
Order By: Relevance
“…4). It is known that the association of 30S and 50S ribosomal subunits requires Mg 2ϩ ions (25)(26)(27) and that Mg 2ϩ stabilizes the secondary structure of rRNA and the binding of the ribosomal proteins to the rRNA (28)(29)(30). These results raise the possibility that restoration of the Mg 2ϩ concentration by the disruption of yhdP and overexpression of mgtE suppresses the defect in 70S ribosome formation that is observed in the ⌬rpmH mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). It is known that the association of 30S and 50S ribosomal subunits requires Mg 2ϩ ions (25)(26)(27) and that Mg 2ϩ stabilizes the secondary structure of rRNA and the binding of the ribosomal proteins to the rRNA (28)(29)(30). These results raise the possibility that restoration of the Mg 2ϩ concentration by the disruption of yhdP and overexpression of mgtE suppresses the defect in 70S ribosome formation that is observed in the ⌬rpmH mutant.…”
Section: Resultsmentioning
confidence: 99%
“…One probable reason is stabilization of the 50S subunit. Mg 2ϩ stabilizes the binding of ribosomal proteins to the rRNA and the secondary structure of rRNA in the ribosome (28)(29)(30). Moreover, it has been demonstrated that Mg 2ϩ concentration controls the dynamics of the ribosome exquisitely through altering ribosome stability and flexibility (66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have aligned 23S/28S rRNA sequences from 122 organisms (29) that represent, as far as available data allow, a complete and non-biased sampling of the phylogenetic tree, including to all three domains of life. This alignment suggests that the pairing interactions of Helix 26a are conserved over the entire phylogenetic tree.…”
Section: Resultsmentioning
confidence: 99%
“…We aligned 23S rRNA/28S sequences from 122 organisms (29) intended to represent, as far as available data allow, a broad sampling of the phylogenetic tree of life including all three domains of life. Sequences came from 19 eukaryotic species, 67 bacterial species and 36 archaeal species.…”
Section: Methodsmentioning
confidence: 99%